PERSEPSI MASYARAKAT TERHADAP HIDROPONIK DI KELURAHAN TELING BAWAH, KOTA MANADO - Mercy Y. Sengkey; Welson M. Wangke; Elsje P. Manginsela (AGRI-SOSIOEKONOMI, 2017)
This study aimed to analyze and determine the public perception of hydroponic in the distict Teling Bawah Manado City. This aims was conducted over five months from November 2016 to the month of Maret 2017 from preparation to the arrangement of research reports. The location of research is in districts Teling Bawah Manado City. This research uses primary data and secondary data. Primary data was obtained from 30 respondents using questionnaires, while secondary data obtained from the office district Teling Bawah Manado City. The sampling method in this study was used purposive sampling method. Result of this research show that the public percepstion of Hydroponic are very good with the index of perceptions 84,16% and are classified to category of strongly agree. The society are strongly agree with the existance of agriculture technique using Hydroponic. People think that Hydroponic is very useful for the society, because with Hydroponic, people could consume healthy fruits and vegetables without using chemis chemical products; no need to try very hard to find a land to cultivate; could take advantages of used goods at home; no need a long time to use hydroponic; and use soil as conventional agriculture, so that the actors of Hydroponic do not have to be in contact with worms.